The 2021 update of the EPA’s adverse outcome pathway database - Holly M. Mortensen (Nature Portfolio, 2021)
Measurement(s) adverse outcome pathway • gene interactions • Orthologous Gene • chemical gene interactions • molecular pathway • disease gene associations • SNP Technology Type(s) digital curation Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14737557